2000
DOI: 10.1046/j.1432-1327.2000.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the myo‐inositol transport system in Trypanosoma cruzi

Abstract: myo-Inositol is a growth factor for mammalian cells as well as for the pathogenic protozoa Trypanosoma cruzi. Most of the cell surface molecules in this organism rely on myo-inositol as the biosynthetic precursor for phosphoinositides and glycosylated phosphatidylinositols. The aim of this work was to investigate the process of myo-inositol translocation across the parasite cell membrane. myo-Inositol uptake was concentration-dependent in the concentration range 0.1±10 mm with maximal transport obtained at 8 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…Similar results were observed for sakuranetin (5) in our experiments against epimastigote forms of T. cruzi Y strain (IC 50 47.5 µg mL -1 , Table 2). Although the dihydrochalcone phloretin (4) did not show detectable trypanocidal activity in our work (IC 50 higher than 365 µM, Table 2), it has been described to influence the glucose metabolism of T. cruzi, T. brucei, and T. rangeli (Bakker et al 1999;Einicker-Lamas et al 2000;Miletti et al 2006). …”
Section: Discussioncontrasting
confidence: 69%
“…Similar results were observed for sakuranetin (5) in our experiments against epimastigote forms of T. cruzi Y strain (IC 50 47.5 µg mL -1 , Table 2). Although the dihydrochalcone phloretin (4) did not show detectable trypanocidal activity in our work (IC 50 higher than 365 µM, Table 2), it has been described to influence the glucose metabolism of T. cruzi, T. brucei, and T. rangeli (Bakker et al 1999;Einicker-Lamas et al 2000;Miletti et al 2006). …”
Section: Discussioncontrasting
confidence: 69%
“…In Trypanosoma cruzi , the etiologic agent of Chagas disease or American trypanosomiasis, myo- inositol transport is facilitated by an energy-dependent, phloridzin-sensitive but cytochalasin B-insensitive system, suggesting that there are at least 2 transporters, a sodium-dependent and a sodium-independent one, that are operational in these parasites (42). Leishmania donovani , the agent of leishmaniasis, transports myo- inositol with a single transporter, L. donovani MIT (LdMIT), with a K m of 0.08 mM (43).…”
Section: Discussionmentioning
confidence: 99%
“…Although myo -inositol can be produced de novo from glucose (see below), uptake of myo -inositol has been described in L. donovani [191], T. cruzi [192], and T. brucei [193]. Detailed characterization of the transporters, including functional expression in Xenopus oocytes, demonstrated that myo -inositol uptake in L. donovani promastigotes and T. brucei procyclic forms is mediated via H + -coupled electrogenic cotransport [150, 191, 194].…”
Section: Phospholipid Synthesismentioning
confidence: 99%